THE CONSTITUTION OF PEDAGOGICAL ACTIVITY IN THE MATH CLUB - Alves, Lukas Adriel Francisco (2023)
The aim of this article is to understand the contributions arising from the movement to re-elaborate an LTS for teaching learning at the Mathematical Club (CluMat), which show evidence of the contribution of a Learning Triggering Situation (LTS) for learning the pedagogical activity . The Mathematical Club of the State University of Goiás, Campus Sudoeste – Headquarters: Quirinópolis (CluMat-UEG) is the context of the investigation and the subjects were 30 (thirty) undergraduates who participated in the Club. This space is based on the assumptions of the Historical-Cultural Theory and the Activity Theory. In order to reach the given objective, the formative experiment was chosen as a methodological structure, and data were collected through audiovisual recordings and questionnaires, during all meetings of the 2022 school year. was: unit, episode and flashes. The results demonstrate that the subjects understood the meaning of the pedagogical activity from the community they belonged to, and thus attributed new meanings to the learning process they were experiencing.